2020 46th Euromicro Conference on Software Engineering and Advanced Applications (SEAA) 2020
DOI: 10.1109/seaa51224.2020.00069
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Contents and Automatic Detection of KL-SATD

Abstract: When developers use different keywords such as TODO and FIXME in source code comments to describe selfadmitted technical debt (SATD), we refer it as Keyword-Labeled SATD (KL-SATD). We study KL-SATD from 33 software repositories with 13,588 KL-SATD comments. We find that the median percentage of KL-SATD comments among all comments is only 1,52%. We find that KL-SATD comment contents include words expressing code changes and uncertainty, such as remove, fix, maybe and probably. This makes them different compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
(20 reference statements)
1
7
0
Order By: Relevance
“…Different approaches have been proposed to detect SATD, including a keyword-based (da S. Maldonado and Shihab, 2015), text mining (Huang et al, 2018), Natural Language Processing (da S. Maldonado et al, 2017b, and convolutional neural networks (Ren et al, 2019). Rantala et al (2020) went deeper on SATD comments containing keywords such as TODO and FIXME (i.e., KL-SATD) and compared them to the rest of source code comments. While the median percentage of KL-SATD is very low ( 2%), their contents is very different from other comments.…”
Section: Studies On Technical Debtmentioning
confidence: 99%
See 1 more Smart Citation
“…Different approaches have been proposed to detect SATD, including a keyword-based (da S. Maldonado and Shihab, 2015), text mining (Huang et al, 2018), Natural Language Processing (da S. Maldonado et al, 2017b, and convolutional neural networks (Ren et al, 2019). Rantala et al (2020) went deeper on SATD comments containing keywords such as TODO and FIXME (i.e., KL-SATD) and compared them to the rest of source code comments. While the median percentage of KL-SATD is very low ( 2%), their contents is very different from other comments.…”
Section: Studies On Technical Debtmentioning
confidence: 99%
“…Examples of SATD by Potdar and Shihab (2014) are such comments as "// TODO this is such a hack it is silly" from Eclipse and "// Unsafe; should error" from Chromium OS. Following the seminal work of Potdar and Shihab (2014) researchers have studied different kinds of TD (Bavota and Russo, 2016;Fucci et al, 2021;Maipradit et al, 2020;Mensah et al, 2018;Rantala et al, 2020): from those introduced by such keywords as "TODO" or "FIXME" to those focusing on situations when developers are waiting for a certain event or an updated functionality, from those focusing on functional defects to those related to maintainability. To encompass different variants of SATD found in the scientific literature, in this paper we opt for a broad definition and consider as SATD any source code comments for annotating delayed or intended work activities such as TODO, FIXME, hack, workaround.…”
Section: Introductionmentioning
confidence: 99%
“…When investigating feature importance, in a single project one would suspect that project specific words would have more weight. Indeed this is a difficulty others have experienced when using regression coefficients as measures of feature importance [44]. It appears that SHAP avoids this problem as only one project specific word 'nonnls' is seen in the table.…”
Section: Satd Feature Interpretability and Analysismentioning
confidence: 99%
“…Potdar and Shihab [75] explore self-admitted, e.g., via code comments, technical debt (SATD), while Bavota and Russo [76] investigate the diffusion and evolution of SATD and its relationship with software quality. Huang et al [77] and Rantala et al [78] identify SATD using advanced techniques, and Christians [79] examines the relation between SATD and refactoring in general systems. The refactorings we have identified that correlate to debt categories may be considered a form of (ML-specific) SATD.…”
Section: Re L a T E D W O R Kmentioning
confidence: 99%